Emerging technologies and enhanced therapeutics: the future is bright, the future is nursing. (2nd February 2020) - Green, Barrie
Abstract : This year marks the year of the nurse and midwife. Barrie Green reflects on his career in nursing and what he thinks the profession can offer.